Anesthesia in Children with Thrombocytopenia During Bypass Surgery for Extrahepatic Portal Hypertension (Review) - A. A. Naleyev; V. V. Lazarev; T. V. Linkova (Общая реаниматология, 2021)
Portal hypertension syndrome is one of the most severe pediatric conditions causing gastroesophageal bleeding which can be fatal. The main challenge in the management of portal hypertension is prevention of bleeding from the portal vein system, which is achieved by vascular surgery, particularly portosystemic shunting. Epidural anesthesia, despite its advantages over the opioid one, is not always performed in children with extrahepatic portal hypertension, and still remains unsolved issue in pediatric anesthesiology.Aim of the review: to evaluate the scope of limitations of general anesthesia in bypass surgery for extrahepatic portal hypertension in children with thrombocytopenia. We searched PubMed, Medline, Elibrary.ru and other databases and used original clinical observations while performing anesthesiologic support of surgical correction of extrahepatic portal hypertension in children.We found that general anesthesia for portosystemic bypass surgery in children with thrombocytopenia requires the anesthetic support that does not include epidural anesthesia and high-dose opioid administration. This issue can be resolved by including the central selective alpha-2-adrenergic agonist dexmedetomidine with both analgesic and hypnotic effects in the anesthesia support. Due to its additive effects, this drug significantly reduces the need for hypnotics and opioid analgesics while maintaining a high level of neurovege-tative protection.Conclusion. In our opinion, optimizing anesthesia in children with thrombocytopenia during bypass surgery for extrahepatic portal hypertension is essential to minimize surgical stress and side effects of drugs.